2017
DOI: 10.2136/vzj2016.06.0054
|View full text |Cite
|
Sign up to set email alerts
|

Combining X‐ray Computed Tomography and Visible Near‐Infrared Spectroscopy for Prediction of Soil Structural Properties

Abstract: Soil structure is a key soil property affecting a soil's flow and transport behavior. X-ray computed tomography (CT) is increasingly used to quantify soil structure. However, the availability, cost, time, and skills required for processing are still limiting the number of soils studied. Visible near-infrared (vis-NIR) spectroscopy is a rapid analytical technique used successfully to predict various soil properties. In this study, the potential of using vis-NIR spectroscopy to predict X-ray CT derived soil stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…The required preparation for this method is simple, involving only air‐drying of the soil and sieving down to 2 mm. Visible near‐infrared spectroscopy has been successfully used to predict soil properties such as the complete soil texture distribution (Hermansen et al, 2017), soil structure (Katuwal et al, 2018), and soil specific surface area (Ben‐Dor et al, 2008; Knadel et al, 2018). Furthermore, studies have shown its ability to predict the wet part of the soil‐water retention curve (Babaeian et al, 2015; Pittaki‐Chrysodonta et al, 2018; Santra et al, 2009).…”
mentioning
confidence: 99%
“…The required preparation for this method is simple, involving only air‐drying of the soil and sieving down to 2 mm. Visible near‐infrared spectroscopy has been successfully used to predict soil properties such as the complete soil texture distribution (Hermansen et al, 2017), soil structure (Katuwal et al, 2018), and soil specific surface area (Ben‐Dor et al, 2008; Knadel et al, 2018). Furthermore, studies have shown its ability to predict the wet part of the soil‐water retention curve (Babaeian et al, 2015; Pittaki‐Chrysodonta et al, 2018; Santra et al, 2009).…”
mentioning
confidence: 99%
“…CT may also be used for imaging the whole soil core samples where a voxel size between 20 µm and 50 µm is achieved (Jarvis et al, 2017;Rab et al, 2014;Vaz et al, 2011). A resolution of this order allows for macropore observation (Jarvis, 2007;Katuwal et al, 2018;Müller et al, 2018) and root visualization (Daly et al, 2018;Sander et al, 2008). However, it can also be used for imaging soil aggregates with a voxel size of 1 µm or smaller (Józefaciuk et al, 2015;Voltolini et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach involves locally-adaptive segmentation methods Katuwal et al, 2018;Martín-Sotoca et al, 2018;Porter and Wildenschild, 2010). Some of these have been designed especially for binarising the soil media Martín-Sotoca et al, 2018) which utilize spatial information beside the gray level value to assign each voxel to a pore-space or soil matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Visible‐NIRS has been applied to predict different soil properties including basic soil properties such as soil organic C, clay, and water content (Stenberg et al, 2010). However, more recently the capability of the method to successfully predict other soil properties was also tested in studies on particle size distribution (Hermansen et al, 2017), soil structure (Katuwal et al, 2017), soil binding capacities (Paradelo et al, 2016), and water repellency (Knadel et al, 2016). Furthermore, vis–NIRS models have been developed to predict the wet end of the soil water retention curve (Santra et al, 2009; Babaeian et al, 2015; Pittaki‐Chrysodonta et al, 2018).…”
mentioning
confidence: 99%